Pedicled Omentoplasty for Treatment of Rheumatoid Nodule Pneumothorax: A Case Report - Hiroki Matsumiya; Koji Kuroda; Teppei Hashimoto; Fumihiro Tanaka (The Thoracic & Cardiovascular Surgeon Reports, 2024)
Background No consensus exists regarding surgical intervention for rheumatoid nodule–related pneumothorax. Clinical policy decisions rely on individual clinicians' experience and are usually intractable.